The Effect of Green Marketing on Brand Image and Impact on Purchasing Decision (Case Study on Student of The Faculty of Administrative Sciences, Universitas Brawijaya WHO Purchase Tupperware Products) - Ulfiah, Ulfiah; Veithzal Rivai Zainal; Azis Hakim (Dinasti International Journal of Digital Business Management, 2023)
This research aims to clarify (1) the influence of green marketing to brand image, (2) the influence of green marketing to the purchase decision (3) the influence of brand image to the purchase decision. This type of research is explanatory with quantitative approach. Variables in this research are green marketing, brand image, and purchase decision. The population in this research are students of Faculty of Administrative Sciences 2012/2013 Brawijaya University, who purchase, use the product and know that Tupperware products are green products. This research uses 100 people as sample whisch are chosen by purposive sampling, and use questionnaire as data collection methods. This research also uses descriptive analysis and path analysis methods to analyze the data. The result of path analysis shows that green marketing has the significant influence to the brand image and purchase decision, and also brand image that influence purchase decision significantly. Based on the results of this study, Tupperware Corporation should provide more detailed and accurate information about the products offered through the media, so it will increase the consumer knowledge about the product, especially about green marketing.